2017
DOI: 10.1155/2017/1059678
|View full text |Cite
|
Sign up to set email alerts
|

Association between the APOEε4 Allele and Late-Onset Alzheimer’s Disease in an Ecuadorian Mestizo Population

Abstract: Alzheimer's disease (AD) is the most common neurodegenerative disease. It has two main pathological hallmarks: amyloid plaques and neurofibrillary tangles. The APOE ε4 allele has been recognized as the strongest genetic risk factor for late-onset Alzheimer's disease (LOAD) in several populations worldwide, yet the risk varies by region and ethnicity. The aims of this study were to describe APOE allele and genotype frequencies and examine the relationship between the APOE ε4 allele and LOAD risk in an Ecuadoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Another study conducted among PLWH reported that having at least one apolipoprotein E4 (ApoE4) allele, a particular ApoE genotype thought to be associated with late-onset Alzheimer’s disease ( Montufar et al., 2017 ), was associated with decreased cognitive performance, and reduced white matter in the brain, and potentially exacerbated by existing HIV-related pathology ( Wendelken et al., 2016 ). While accumulating evidence suggests ApoE may influence tau-mediated mechanisms of neurodegeneration ( Yamazaki et al., 2019 ), the true role of this protein in the progression of neurocognitive impairment among PLWH is still largely undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted among PLWH reported that having at least one apolipoprotein E4 (ApoE4) allele, a particular ApoE genotype thought to be associated with late-onset Alzheimer’s disease ( Montufar et al., 2017 ), was associated with decreased cognitive performance, and reduced white matter in the brain, and potentially exacerbated by existing HIV-related pathology ( Wendelken et al., 2016 ). While accumulating evidence suggests ApoE may influence tau-mediated mechanisms of neurodegeneration ( Yamazaki et al., 2019 ), the true role of this protein in the progression of neurocognitive impairment among PLWH is still largely undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Although Montufar et al . [ 13 ] found no statistically significant differences in HTN ( P = 0.459) between patients with AD and controls, Kimm et al . [ 14 ] considered HTN a strong risk factor of AD either in the age of less than or more than 65 years ( P < 0.05).…”
Section: Discussionmentioning
confidence: 98%
“…This result was inconsistent with the result found by Montufar et al . [ 13 ] On the other hand Kimm et al . [ 14 ] found a significant risk of AD in smoker's men aged 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…This study finds that the e4/e4 homozygous carrier rate of the Li people in Hainan Island is 1.39%. According to foreign scholars such as Stefany [22], the e4/e4 homozygous carrier rates of Caucasian Americans, African Americans, Hispanics, and Japanese are 1.8%, 2.1%, 1.9%, 0.8%. This data shows that the e4/e4 homozygous carrier rate of the Li people in Hainan Island is higher than that of the Japanese, and lower than that of Caucasian Americans, African Americans and Hispanics.…”
Section: Discussionmentioning
confidence: 99%